Combination of LHRH analog with somatostatin analog and dexamethasone versus chemotherapy in hormone-refractory prostate cancer: A randomized phase II study - Dimopoulos, M.A.; Kiamouris, C.; Gika, D.; Deliveliotis, C.; Giannopoulos, A; Zervas, A.; Alamanis, C.; Constantinidis, C.; Koutsilieris, M. (Urology, 2004)
Objectives. To evaluate prospectively the combination of a luteinizing hormone-releasing hormone analog with a somatostatin analog and dexamethasone in patients with hormone-refractory prostate cancer (HRPC) in a randomized Phase II study. HRPC presents a challenging therapeutic problem. Salvage chemotherapy is the usual approach at this stage of the disease. The combination of a luteinizing hormone-releasing hormone analog with a somatostatin analog and dexamethasone has produced objective clinical responses in HRPC. Methods. Forty patients with HRPC were randomized to receive one of two treatments. Group 1 underwent chemotherapy (estramustine 140 mg three times daily and etoposide 100 mg orally for 21 days) and group 2 the combination of a somatostatin analog (lanreotide 30 mg intramuscularly every 14 days) and dexamethasone (4 mg tapered to 1 mg), in addition to androgen ablation by orchiectomy or a luteinizing hormone-releasing hormone analog (triptorelin 3.75 mg intramuscularly every 28 days). The clinical and prostate-specific antigen (PSA) response, overall survival, time to progression, and toxicity were compared between the two groups. Results. The data of 20 patients in group 1 and 18 in group 2 were analyzed. The demographic and clinical data were similar in the two groups at study entry. A PSA response (decrease of greater than 50%) was observed in 45% of group 1 and 44% of group 2. The difference was not statistically significant. A partial clinical response was observed in 29% and 30% of groups 1 and 2, respectively. Again, the difference was not statistically significant. Changes in performance status and pain score during treatment were not significantly different in the two groups. Hematologic toxicity was more frequent in group 1 (80% of patients), and mild diabetes was more frequent in group 2 (22% of patients). The overall survival was 18.8 months in group 1 and 18 months in group 2 (not statistically significant). The time to progression was 6 versus 4 months and, in the PSA responder subgroup, it was 8 versus 7.7 months in groups 1 and 2, respectively (neither difference was statistically significant). Conclusions. The results of our randomized Phase II study indicated that the new combination treatment (luteinizing hormone-releasing hormone analog, somatostatin analog, and dexamethasone) may be equally effective as salvage chemotherapy in patients with HRPC in terms of the clinical and PSA response, overall survival, and time to progression. A larger prospective Phase III trial is required to confirm our observations. © 2004 Elsevier Inc.